Pengaruh Disiplin dan Pelatihan Kerja Terhadap Produktivitas Kerja Karyawan Pada Kantor Otoritas Jasa Keuangan Regional 7 Sumbangsel - Eka Damayanti; Hj. Luis Marnisah; Roswaty Roswaty (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to investigate the effects of discipline and job training on employee work productivity at the Regional Financial Services Authority Office 7 of Sumbagsel. The sample was selected using the saturated sample technique. Data of 60 respondents were collected through interviews and questionnaires. This study implemented the multiple linear regression method to analyze data. The finding prove that partially, each discipline and job training has a positive and significant effect on employees' productivity. This research can provide benefits for the Regional Financial Services Authority Office 7 of Sumbagsel. To increase employees' productivity, the institutional leader should optimize the discipline and job training factors